2019
DOI: 10.1136/bmjopen-2018-027659
|View full text |Cite
|
Sign up to set email alerts
|

The role of education in the association between self-rated health and levels of C-reactive protein: a cross-sectional study in rural areas of China

Abstract: ObjectivesThis study aims to examine the association between self-rated health (SRH) and levels of C-reactive protein (CRP) among adults aged 45 to 101 years old in rural areas of China, and to explore the role of education in the association.DesignCross-sectional study.SettingThe study population was derived from two databases in China: Nanping project (NP) and the China Health and Retirement Longitudinal Study (CHARLS).ParticipantsThere were 646 participants from a rural area of Nanping (NP) and 8555 rural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Specifically, the gene scores for several diseases which increase the new-onset risk of death (e.g., ischemic heart disease, macrovascular stroke and type 2 diabetes) were also associated with SRH 38 . Thirdly, worse SRH, as a sensitive indicator of health, could synthetically reflect their poor physical status and social support, which may limit the contact with health services and induce mental stress 39 . Stress is known to be associated with low-grade chronic inflammation and elevated level of pro-inflammatory cytokines 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the gene scores for several diseases which increase the new-onset risk of death (e.g., ischemic heart disease, macrovascular stroke and type 2 diabetes) were also associated with SRH 38 . Thirdly, worse SRH, as a sensitive indicator of health, could synthetically reflect their poor physical status and social support, which may limit the contact with health services and induce mental stress 39 . Stress is known to be associated with low-grade chronic inflammation and elevated level of pro-inflammatory cytokines 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Shanahan et al [8] suggested that an elevated hs-CRP level is associated with poor SRH. Conversely, other studies have suggested that poor SRH is associated with elevated hs-CRP levels [10]. Moreover, other studies have reported an association between albumin levels, hemoglobin levels, white blood cell counts, and HDL-cholesterol levels [11].…”
mentioning
confidence: 97%